Exterior characteristics and coat colour marker of MC1R gene in Bali Crossbred cattle - Swasti, G. M.; Wardana, E.; Aditama, H.; Panjono, P.; Hartatik, T. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
Crossbreeding between Bali cattle with exotic bulls (such as Simmental and Limousin) has been widely developed in several regions in Indonesia. This study aims to determine changes in exterior characteristics and differences in vital statistics of Bali cattle and their crosses in West Lombok Regen-cy. A total of 91 female cattle aged 1 to 5 years were sampled, consisting of 5 Bali cattle (100%Bali), 54 F1 (50%Bali), 21 G2 (75%Bali/25%Bali), and 11 G3 (12.5%Bali) cattle. Qualitative (color and shape) and quantitative cattle data (vital statistics) were collected through observation and measure-ment. Identification of Bali crossbred cattle genotypes that have different color patterns using molecu-lar markers of the MC1R gene with forward primer MC1R: 5'-GGTGAGTCTCGTGGAGAACG-3' and reverse primer MC1R: 5'-CGTAGAAGATGGAGATGTAGCG-3', at a target DNA sequence size of 308 bp. The dominant color results of Bali cattle showed brick red (60%) and brown (20%), and there was a dark brown and black color change of up to 100% in the crosses. DNA-pool sequencing of 14 samples indicated individual sequence differences, indicated by overlapping nucleotide arrays after the 174 sequence. Furthermore, sequencing of different color representatives from 12 individual sam-ples shows 4 SNPs, namely g.64C>T, g.147C>T, g.159C>T, dan g.235A>C in Bali crossbred cattle. The measurement of chest circumference of Bali cattle, crossbred F1, G2, and G3 aged 3 to 5 years were 151.80±9.60cm, 175.69±12.63 cm, 175.50±11.04cm, and 173.17±15.06cm, respectively.The re-sult indicate the significant differences of body measurement ((P<0.01). In conclusion, the F1 (50%Bali) crossbred produced superior performance. Single nucleotide polymorphism (SNP) can be used as a genetic marker for colour pattern the dark brown-black in crossbred Bali cattle. However, the com-prehenshive study in the future is still needed in the future for cattle crossbred Bali cattle at different generation.